Detection of the Grímsvötn 2011 volcanic eruption plumes using infrared satellite measurements. (12th May 2014) - Cooke, Michael C.; Francis, Peter N.; Millington, Sarah; Saunders, Roger; Witham, Claire
Abstract Infrared satellite measurements were used to track the volcanic plume from Grímsvötn, Iceland in 2011. Following the explosive eruption, the plume was sheared by the atmosphere into two distinct volcanic clouds, one was ash‐rich and the other was mainly composed of sulphur dioxide (SO2) gas. Satellite retrievals of the volcanic ash were found to be consistent with an andesitic/basaltic composition, providing a framework for composition evaluation immediately following an eruption. SO2 was detectable for several weeks following the eruption highlighting the importance of monitoring volcanic clouds for a prolonged period to manage the associated risk of air traffic.